Book Review: Rune Elvik and Truls Vaa (eds.) The Handbook of Road Safety Measures - Wegman, Fred (European Journal of Transport and Infrastructure Research, 2004)
What effect does a road safety measure have on the number of casualties, what are the costs, and are there any side effects to be mentioned? The Norwegian researchers Rune Elvik and Truls Vaa have tried to answer these elementary questions. They have done this in a handbook of more than 1000 pages. The authors themselves have admitted that "handbook" is not really the right name, because in a handbook you expect to find instructions or advices about how to draw up and implement the best road safety measures. The authors admit that an encyclopaedia or catalogue is a more accurate name.